ANALISIS IMPLEMENTASI FESTIVAL EKSOTIKA BROMO DALAM MENINGKATKAN KINERJA SENIMAN DAERAH PROGRAM BIDANG KEBUDAYAAN DISPORAPARBUD KABUPATEN PROBOLINGGO - jurnalpps pps; Rr. Herlina Wulansari; C. Sri Hartati; Soenarmi ÔÇÄ (Jurnal Manajerial Bisnis, 2020)
This study aims to determine the analysis of the implementation of the Bromo Exotica Festival in improving the performance of regional artists in the cultural sector program ProPharmaru District, the positive response of artists in the area and also the extent of the performance of regional artists in developing local cultural wisdom. This needs to be done by researchers to be able to analyze the description of the implementation of the bromo exotica festival and know the structure of cultural programs in the Probolinggo Disporaparbud, as well as to know the extent of positive responses from local artists and what are the efforts of artists in order to develop local cultural wisdom in each region. In this research there are 8 (eight) people as resources who will be expected to provide valid and accountable supporting data. The research was carried out in the tourism objects of the Sand Bromo Sea, the Probolinggo Disporaparbud office, and several areas where artists live. The results of this study indicate that there is an inseparable link between Disporaparbud's cultural programs and the performance of artists in their efforts to develop local cultural wisdom, especially in the Probolinggo district.Keywords: bromo exotic festival, performance of local artists